The Alboran Sea circulation and its biological response: A review - Sánchez-Garrido, José C.; Nadal, Irene (Frontiers in Marine Science, 2022)
The oceanography of the Alboran Sea (AS) has been the subject of intensive research for decades. Chief among the reasons for this interest is the variety of physical processes taking place in the basin, spanning from coastal upwelling, dynamic of density fronts, internal waves, and strong meso- and submesoscale turbulence. Historical fieldwork and an increasing number of numerical studies in recent years have led to a more complete—although more dispersed—description and knowledge of process dynamics in the AS and their role in shaping primary productivity and regional fisheries resources. In this review, we summarize and put together old and new research to get an updated picture of the AS circulation and its variability at different time scales, with an emphasis on physical–biological interactions. As part of the review, we identify gaps in our understanding regarding the physical drivers for seasonal and for rapid transitions between the most recurrent one-gyre and two-gyre modes of circulation of the AS. We also point at possible research strategies based on end-to-end regional biophysical modeling to gain new insights into past and present physical control on fisheries resources and for assessing plausible climate change impacts on the AS ecosystem.